Bosses' Perceptions of Family-Work Conflict and Women's Promotability: Glass Ceiling Effects - Hoobler, Jenny M.; Wayne, Sandy J.; Lemmon, Grace (Academy of Management Journal, 2009)
We examine one potential reason for the persistence of the glass ceiling: bosses' perceptions of female subordinates' family-work conflict. Person categorization and social role theories are used to examine whether bosses (both male and female) perceive women as having greater family-work conflict and therefore view them as mismatched to their organizations and jobs. The results support our model: bosses' perceptions of family-work conflict mediated the relationships between subordinate sex and perceptions of person-organization fit, person-job fit, and performance. Both types of fit were related to promotability (nomination for promotion and manager-assessed promotability). We discuss implications for practice and future research.